Takayasu’s arteritis in pregnancy: a rare case report from BJGMC and Sassoon Hospital Pune, Maharashtra, India - Dogra, Amisha; Wankhede, Uma N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Takayasu’s arteritis is a chronic idiopathic vasculitis affecting aorta and its primary branches, commonly seen in young women of Asian or oriental descent during child bearing age. Incidence is 2.6 cases/million/year. It affects females in the reproductive years accounting for almost 80% of the cases. A 34 year female G2P1L1 with 9 months of amenorrhea with previous LSCS known case of takayasu arteritis, epilepsy with right side hemiparesis with aphasia. She proceeded to have elective LSCS with ventouse delivery under epidural anaesthesia and delivered alive healthy female baby weight 2.4 kg and patient was transferred to intensive care unit for observation for 48 hrs. patients intrapartum post partum period was uneventful and discharged after 1month with cardiology fitness. Pregnancy with takayasu arteritis (pulseless disease) requires a multidisciplinary management from gynaecologist, cardiologist, neurologist for favourable maternal and fetal outcome.